Yogyakarta Lecturers' Experience in Using Mobile Phone in English Language Teaching - Rohmah, Farida Noor; Aditya, David Sulistiawan (English Department FBS UNP, 2020)
This study is aimed at investigating lecturers’ experience in using mobile phone in English teaching practice. Employing qualitative method using Creswell (2014), the study collected data through in-depth-interview and analyzed data through several steps including data preparation and organization, data reading, data coding, data description, data interpretation, and data presentation. The result of the study indicated that the lecturers mostly implemented MALL and utilized mobile phone for three main purposes, namely instructional need, content understanding development, and communication. However, it was found that problem of internet connection became a barrier to fully implement MALL in ELT.